2014
DOI: 10.1177/0961000614532861
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the librarian/user gap in perception of health information services: A phenomenographic approach

Abstract: The study aimed to illuminate different perspectives between public library users and librarians in perceiving the major challenges for consumer health information services and suggest how to reduce the gap between them. The study employed phenomenography, a qualitative approach, and conducted semi-structured intensive interviews with 40 public library users and 20 reference librarians at 12 public libraries in Florida and Maryland. Findings identified gaps between user needs and the assistance that librarians… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Dalmer () also reported an increase in consumer health information requests in public libraries. However, the lack of awareness about library resources (Rubenstein, ; Yi, ), librarians’ need to understand their users better to plan services for them (Yi & You, ) and partnerships with health care organisations (Henry & Marley, ) are recurrent barriers to health literacy service delivery in the libraries. Other challenges were noted by Luo () and Rubenstein ().…”
Section: Resultsmentioning
confidence: 99%
“…Dalmer () also reported an increase in consumer health information requests in public libraries. However, the lack of awareness about library resources (Rubenstein, ; Yi, ), librarians’ need to understand their users better to plan services for them (Yi & You, ) and partnerships with health care organisations (Henry & Marley, ) are recurrent barriers to health literacy service delivery in the libraries. Other challenges were noted by Luo () and Rubenstein ().…”
Section: Resultsmentioning
confidence: 99%
“…Librarians, themselves, do not necessarily know how to discern between meaningful and questionable information (Flaherty 2013;Keselman, Smith, and Hundal 2014). Multiple studies have found gaps in knowledge about health information resources and the ability to use medical databases (Flaherty and Luther 2011;Smith 2011;Yi and You 2015). For example, Flaherty and Luther (2011) found that library staff in upstate New York were unable to provide trustworthy information about vaccinations, at times relying on popular resources that contradicted scientific research.…”
Section: Finding Health Informationmentioning
confidence: 99%
“…Library staff have their own concerns about providing health information. In interviews with twenty reference librarians and forty patrons, Yi and You (2015) sought to understand differences between each group's experiences providing and seeking health information. Librarians readily admitted that they did not consider themselves to be particularly health literate, citing lack of knowledge and inability to assess health resources.…”
Section: Finding Health Informationmentioning
confidence: 99%
See 2 more Smart Citations